2013
DOI: 10.1098/rsta.2012.0246
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the flow field surrounding tidal turbine arrays for varying positions in a channel

Abstract: The modelling of tidal turbines and the hydrodynamic effects of tidal power extraction represents a relatively new challenge in the field of computational fluid dynamics. Many different methods of defining flow and boundary conditions have been postulated and examined to determine how accurately they replicate the many parameters associated with tidal power extraction. This paper outlines the results of numerical modelling analysis carried out to investigate different methods of defining the inflow velocity bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, these methods are not suitable to investigate the wake within 22 and downstream of tidal turbine arrays and focus on the dominant flow processes occurring in 23 such complex operating environments. 24 To reduce the computational resources required to investigate the performance of multiple 1 tidal turbines operating in small arrays, actuator fences (Daly et al, 2013) and multiple 2 circular disks (Nishino and Willden (2013); Turnock et al (2011)) have been used to speed 3 up numerical calculations and investigate the effects of energy extraction for cross stream 4 arrays that block a large proportion of the available tidal channel. It was shown that analytical 5 model and 3D RANS calculation with actuator fence revealed interactions between beneficial 6 flow effects and increased flow reduction due to increasing devices which in turn led to an 7 increased optimum blockage of the tested configurations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are not suitable to investigate the wake within 22 and downstream of tidal turbine arrays and focus on the dominant flow processes occurring in 23 such complex operating environments. 24 To reduce the computational resources required to investigate the performance of multiple 1 tidal turbines operating in small arrays, actuator fences (Daly et al, 2013) and multiple 2 circular disks (Nishino and Willden (2013); Turnock et al (2011)) have been used to speed 3 up numerical calculations and investigate the effects of energy extraction for cross stream 4 arrays that block a large proportion of the available tidal channel. It was shown that analytical 5 model and 3D RANS calculation with actuator fence revealed interactions between beneficial 6 flow effects and increased flow reduction due to increasing devices which in turn led to an 7 increased optimum blockage of the tested configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the value of K will invariably influence the wake downstream of the disc. The relationship between C T and K has been shown previously using Equation (7). In this paper, K is set to a constant value of 2, which correspond to C T = 0.89.…”
Section: Model Set-upmentioning
confidence: 99%
“…However, because of the strong gradients of the flow and also turbulence variables that exist in the viscous layer, highly-refined grids are needed near the bottom [27]. Small-scale models are known to use a no-slip wall at the bed (refer to References [4,5,7]) since it is still computationally feasible to satisfy the y + requirement. Nonetheless, the flow details in the boundary layer were not of specific interest in this paper.…”
Section: Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Above and below the turbine, the flow was less affected by the presence of the turbine, but the mean current strength was still weaker than predicted in the absence of turbines. These profiles do not have the large velocity deficit at the turbine and the accelerated flow beneath the turbine predicted by computational fluid dynamics (CFD) models e.g., [38] because the velocities are volume-averages. However, previous work [33] has shown that the averaged velocities from a CFD model are very similar to the averages derived by the larger scale model used here.…”
Section: Turbine Effects On Velocity Profilesmentioning
confidence: 99%